Social-Emotional Learning and its Relationship to Prosocial Behavior among Secondary School Students in Jordan - Al-Salti, Amal S.; Aljawabrah, Noura M.; Abu Awwad, Ferial M. (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aims at measuring social-emotional competencies in relation to prosocial behavior among secondary school students in Amman. Methodology: The study employs the descriptive, correlational approach. The study sample consists of (500) male and female students selected from several secondary schools by using cluster randomization. To achieve its objectives, the study uses the Social-Emotional Learning Scale, which consists of 23 items, and the Prosocial Behavior Scale, which consists of 23 items. Results: The results indicate high rating of social-emotional learning skills and average rating of prosocial behavior. The study also shows that there is a moderate positive correlation between social-emotional learning skills and prosocial behavior, suggesting that prosocial behavior could be predicted based on the sub-competencies of social-emotional learning. Conclusion: The study invites teachers to pay more attention to activating social-emotional learning due to its positive effects on students, whether academic or behavioral. Hence, it calls for educating teachers about social-emotional learning and training them to incorporate it. The study also recommends conducting other studies on different age categories and exploring social-emotional learning in relation to other variables.